Media Interaktif Patriasite untuk Pengenalan Budaya Lokal Kabupaten Bojonegoro pada Anak Usia 5 – 6 Tahun - Fadila Nanda Aulia; Ahmad Samawi; Nur Anisa (Khirani: Jurnal Pendidikan Anak Usia Dini, 2024)
The aim of this research and development is to produce appropriate patriarchal The aim of this research and development is to produce appropriate patriarchal interactive media based on the criteria of being attractive, efficient and effective as a medium for introducing various local cultures in Bojoengoro Regency to children aged 5 -6 years. In fact, several educational institutions still implement local cultural learning This research aims to develop interactive media based on an educational application called "Patriasite" as a means of introducing local culture to Bojonegoro Regency for children aged 5-6 years. This research methodology uses a design development approach. Data was collected through interviews, questionnaires, and documentation from validation and trials. The results of this research show that the Patriasite website can introduce the local culture of Bojonegoro from the aspects of attractiveness and efficiency. This is shown in the results of validation and large and small group trials. From the test results, a percentage of 100% was obtained, meaning that the Patriasite website is very valid in terms of attractiveness and effectiveness.